Transformasi Hukum Islam dalam Bentuk al-Qânûn al-Duwalî - Rizal Darwis & Asna Usman Dilo (Universitas Islam Negeri Jakarta, 2013)
Abstract: Transformation of Islamic Law within the Form of al-Qânûn al-Duwalî. International law (al-qânûn al-duwalî) is inter-country or inter-nation law that shows the complex principles and rules which regulate the intercommunity relationships of nations or states and international law issues are not apart from the religion professed by the people in the world. One of them is Islam, whose source of basic rules from Alquran and Hadith have greatly provided guidance of state law such as ethics of war, concept of dâr al-Islâm and dâr al-harb. Religion, state and law will unite to form concentric circles as one entity that is closely related to one another. In essence, Islamic law provides transformation in the field of international law.Keywords: religion, state, al-qânûn al-duwalî, dâr al-Islâm, dâr al-harbAbstrak: Transformasi Hukum Islam dalam Bentuk al-Qânûn al-Duwalî. Hukum internasional (al-qânûn al-duwalî) adalah hukum antarnegara atau antarbangsa yang menunjukkan pada kompleks asas dan kaidah yang mengatur hubungan antarmasyarakat bangsa-bangsa atau negara, dan permasalahan hukum internasional tidak terlepas pula dari ajaran agama yang dianut oleh masyarakat di dunia. Salah satunya adalah agama Islam, yang sumber ajaran pokoknya dari Alquran dan Hadis telah banyak memberikan pedoman hukum bernegara, seperti: etika perang, konsep dâr al-Islâm, dan dâr al-harb. Agama, negara, dan hukum akan bersatu membentuk lingkaran konsentris sebagai satu kesatuan yang berhubungan erat dengan satu sama lain. Intinya, hukum Islam memberikan transformasi dalam bidang hukum internasional.Kata Kunci: agama, negara, al-qânûn al-duwalî, dâr al-Islâm, dâr al-harbDOI: 10.15408/ajis.v13i2.939